2021
DOI: 10.3390/inorganics9020009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Spectroscopic Characterization, DFT Calculations and Cytotoxicity Assays of a New Cu(II) Complex with an Acylhydrazone Ligand Derived from Thiophene

Abstract: A new Cu(II) complex is synthetized by the reaction of copper nitrate and a N-acylhydrazone ligand obtained from the condensation of o-vanillin and 2-thiophecarbohydrazide (H2L). The solid-state structure of [Cu(HL)(H2O)](NO3)·H2O, or CuHL for simplicity, was determined by X-ray diffraction. In the cationic complex, the copper center is in a nearly squared planar environment with the nitrate interacting as a counterion. CuHL was characterized by spectroscopic techniques, including solid-state FTIR, Raman, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Our previous results showed that CuHL displayed wide anticancer activity over lung, colon and bone cancer cells with IC 50 between 2-7 μM. [27] In another work on related compounds, our results with a copper(II)-ONO acylhydrazone ligand derived from 4-hydroxy-benzohydrazide and o-vanillin showed important anticancer properties on leukemia, lung, breast and bone cancer cells with IC 50 between 5-12 μM. [30] More recent results showed that another copper(II)-hydrazone ligand derived from 4-methoxybenzohydrazide with o-vanillin displayed similar IC 50 values on breast cancer cells.…”
Section: Effect Of Cuhl On Cell Viability and Cell Proliferationmentioning
confidence: 97%
See 3 more Smart Citations
“…Our previous results showed that CuHL displayed wide anticancer activity over lung, colon and bone cancer cells with IC 50 between 2-7 μM. [27] In another work on related compounds, our results with a copper(II)-ONO acylhydrazone ligand derived from 4-hydroxy-benzohydrazide and o-vanillin showed important anticancer properties on leukemia, lung, breast and bone cancer cells with IC 50 between 5-12 μM. [30] More recent results showed that another copper(II)-hydrazone ligand derived from 4-methoxybenzohydrazide with o-vanillin displayed similar IC 50 values on breast cancer cells.…”
Section: Effect Of Cuhl On Cell Viability and Cell Proliferationmentioning
confidence: 97%
“…This band can be assigned to ligand-to-metal charge transfer (LMCT) transitions according to our previous published results. [27] Upon monitoring this solution with time (0.25, 0.5, 1, 3, 6 and 24 h), no changes were observed in the UV vis signals, and the integrity of the compound in PBS was conserved within the time-frame of the anticancer activity assays. These results suggest that CuHL is stable over time.…”
Section: Stability Studies Of Cuhlmentioning
confidence: 99%
See 2 more Smart Citations
“…Schiff bases, as well as diarylureas [8][9][10], have been defined as "privileged" ligands in organic synthesis, thanks to their affordability, easy synthesis and different biological activities and ability to form complexes with almost all metals [11][12][13]. Actually, they may form complexes with transition metals, platinum group metals (PGM) [14], lanthanides [15,16], and actinides [17,18] and many of them have been extensively described in the literature [19,20]. Metal complexes bearing in the structure a Schiff base are known for their numerous applications and biological activities including antimicrobial [21], antioxidant [22], antitumor [23], antinflammatory [24], and ureases inhibitors [25], and occupy a central role in the development of coordination chemistry [26][27][28].…”
Section: Introductionmentioning
confidence: 99%